Pengaruh Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Guru SMP IT Pawitra Yayasan Assasuttarbiyah - Rivaldi Tustina; Depy Muhamad Pauzy; Nita Fauziah Oktaviani (PPIMAN Pusat Publikasi Ilmu Manajemen, 2024)
This research aims to determine the simultanes and partial influence of work discipline and work environment on the performance of Assutarbiyyah Foundation Middle School teachers. The research method used is a quantitative method with a survey approach. The sampling technique used saturated samples with a sample size of 42 people. The data collection technique uses an offline questionnaire. The data used is primary data. The analytical tool used in this research is multiple regression using SPSS 25. The research results show that simultaneously work discipline and the work environment have a significant effect on teacher performance. Partially, work discipline has a significant effect on teacher performance. Partially, the work environment has a significant effect on teacher performance.